Efektivitas Pemberian Makanan Tambahan (PMT) Berbasis Pangan Lokal dalam Meningkatkan Cakupan N/D Balita - Yunita; Desri Suryani; Adelia Aperiliana Bella; Darmawati Santoso; Deswita Maharani Br Mataniari; Dinda Puspita Gita; Erva Aulia Janna; Eva Anggi Puspita; Fitria Ogina; Izzatul Ilmi; Juita Sari; Mawar; Mita Apriani; Muhammad Revil Syaputra (CV. CENDIKIA JENIUS INDONESIA, 2025)
The nutritional status of toddlers is an important indicator in determining the quality of public health. In the working area of Beringin Raya Health Center, the coverage of toddlers with weight gain (N/D) in 2024 only reached 66.09%, below the national target of 88%. This community service aimed to evaluate the effectiveness of local food-based Supplementary Feeding (PMT) in increasing N/D coverage. A retrospective comparative descriptive method was used with total sampling of 23 nutritionally vulnerable toddlers. The intervention was carried out for 14 days using local ingredients such as tofu, chicken nuggets, and processed corn, accompanied by cadre assistance and Village Community Deliberation (MMD). The results showed an increase in the average weight from 9.89 kg to 10.00 kg. Inhibiting factors included low maternal nutrition literacy, weak economic conditions, and poor sanitation. The intervention also resulted in cross-sector commitments to support program sustainability. Conclusion: Local food-based PMT has proven effective in increasing toddler weight, but program integration with nutrition education, continuous mentoring, and policy support is necessary.